Walsh, Des - Walsh, Des; White, Linda, 1950- (Memorial University of Newfoundland. Libraries, 1958)
The Des Walsh collection reflects his work as a poet, writer, editor, actor and musician. He has worked in a variety of genres including poetry, short stories, theatre, film, radio and television. This collection provides insight into his extensive career.